Activity of a subset of vesicular GABA-transporter neurons in the ventral zona incerta anticipates sleep onset. Issue 6 (3rd December 2020) - Blanco-Centurion, Carlos; Luo, SiWei; Vidal-Ortiz, Aurelio; Swank, Colby; Shiromani, Priyattam J
Abstract: Study Objectives: Sleep and wake are opposing behavioral states controlled by the activity of specific neurons that need to be located and mapped. To better understand how a waking brain falls asleep it is necessary to identify activity of individual phenotype-specific neurons, especially neurons that anticipate sleep onset. In freely behaving mice, we used microendoscopy to monitor calcium (Ca 2+ ) fluorescence in individual hypothalamic neurons expressing the vesicular GABA transporter (vGAT), a validated marker of GABA neurons. Methods: vGAT-Cre mice (male = 3; female = 2) transfected with rAAV-FLEX-GCaMP6M in the lateral hypothalamus were imaged 30 days later during multiple episodes of waking (W), non-rapid-eye movement sleep (NREMS) or REMS (REMS). Results: 372 vGAT neurons were recorded in the zona incerta. 23.9% of the vGAT neurons showed maximal fluorescence during wake (classified as wake-max), 4% were NREM-max, 56.2% REM-max, 5.9% wake/REM max, while 9.9% were state-indifferent. In the NREM-max group, Ca 2+ fluorescence began to increase before onset of NREM sleep, remained high throughout NREM sleep, and declined in REM sleep. Conclusions: We found that 60.2% of the vGAT GABA neurons in the zona incerta had activity that was biased towards sleep (NREM and REMS). A subset of vGAT neurons (NREM-max) became active in advance of sleep onset and may induce sleep by inhibiting the activity of the arousal neurons. Abnormal activation of the NREM-max neurons may drive sleep attacks and hypersomnia.